Economic Values, Utilization And Species Composition Of Medicinal Plants: A Case Study Of Pondok Tanjung, Perak. [QK99.M2 S635 2003 f rb] [Microfiche 7529] - Ahmad, Smadiyah (2003)
Malaysia is one of the worldï¿½s 12 mega biodiversity, countries with the oldest rainforest.